SISTEM INFORMASI AKUNTANSI PEMBELIAN SPAREPART PADA PT. ADETEX BOYOLALI - Tri Erita Kusumaningsih; Ismunawan (PROSEDING, 2022)
This study aims to determine the accounting information system for the purchase of spare parts at PT. Adetex. In this study using qualitative methods with descriptive analysis. Collecting the necessary data, researchers conduct interviews or question and answer processes directly with relevant sources in the purchasing process to obtain information needed in research and documentation in the form of research documents related to accounting information systems for spare parts purchases, such as purchase requisitions, purchase orders, purchase invoices and other data related to purchases. The result of this research is the procedure for purchasing spare parts using a computer-based accounting information system via the internet with the name Purchasing system. However, when interviewed with several parts of the accounting information system company for the purchase of spare parts at PT. The Adetex system has not been running effectively and efficiently. There are still many problems related to the Purchasing System in the company, one of which is the network which sometimes has errors that hamper the work operations of employees. Keywords: Accounting Information System, Purchase